+0  
 
0
40
2
avatar

Calculate sqrt(60x)*sqrt(12x)*sqrt(63x)*sqrt(42x). Express your answer in simplest radical form in terms of x. Note: When entering a square root with more than one character, you must use parentheses or brackets. For example, you should enter sqrt(14) as "sqrt(14)" or "sqrt{14}".

 Jun 27, 2021
 #1
avatar+33606 
+1

= sqrt (x^4  *  60 * 12*63*42)

= x^2 sqrt ( 4 * 15  * 4 * 3 * 3 * 3*7* 3 * 14)

= 4 *3 *3  x^2 sqrt ( 3*5* 7* 7*2)

= 7* 36 x^2 sqrt(3 *5 *2) 

=252 x^2 sqrt (30)

 Jun 27, 2021
 #2
avatar+4 
0

Thanks for the info i will try to figure it out for more   
 

AdrienneKreiger  Jun 28, 2021

7 Online Users

avatar